Comparison of efficacy of photobiomodulation and topical anesthetic spray in reducing the injection pain in children aged 6–12 years – A randomized clinical trial - Bhavana Bollepalli; Ahalya Penmetsa; Ravigna Peddi; Himavarsha Mannam; Ramalaxmi Koruprolu; Gautami S Penmetsa (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Background: Local anesthesia administration is associated with pain, resulting in dental anxiety in children. Various techniques have been tried to minimize this discomfort such as topical anesthetic gel, spray, Vibration of tissue, and distraction techniques. Literature has shown lesser evidence for photobiomodulation (PBM) in pain reduction for pediatric patients. Aim: To compare the efficacy of PBM 810 nm versus topical local anesthetic spray in reducing injection pain in children of age 6–12 years. Materials and Methods: Fifty-four children aged 6–12 years who visited the outpatient department, department of pediatric and preventive dentistry, requiring local anesthetic administration during invasive procedures were randomly allocated into three groups, namely Group 1 – topical spray (lignocaine hydrochloride 2%), Group 2 – PBM (810 nm, 0.6 W, 40 s), and Group 3 – PBM (810 nm, 0.6 W, 3 min). Pain was assessed subjectively and objectively using the Wong–Baker Faces Pain Rating Scale (WBS) and Sound-Eye-Motor (SEM) Scale, respectively. Objective and subjective pain scores were evaluated using One way ANOVA and jaw wise comparison of PBM efficacy done using independent t-test. Results: The mean WBS scores for Group 1, Group 2, and Group 3 were 3.8 ± 2.21, 1.77 ± 2.81, and 4.11 ± 3.1, respectively, and the difference was statistically significant (P = 0.025) between Group 1 (control) and Group 2 (PBM 40 s). However, no significant difference was found in considering SEM scores. Irrespective of bone topography, PBM was effective in reduction of injection pain, though it was not significant during local infiltration. Conclusion: PBM with 810 nm laser, 0.6 W for 40 s is more effective in reducing the injection pain compared to topical anesthetic spray and PBM for 3 min.